THE VARIATION OF CAESARIAN SECTION COSTS IN INDONESIAN HOSPITALS: A NARRATIVE REVIEW - Tetriyadi Tetriyadi; Atik Nurwahyuni (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: In providing services, hospital, as one of the health care providers, must be able to regulate the number of costs obtained in accordance with the proportion/variation. The costs incurred by hospitals in providing complete personal health services consist of various cost components, including service fees, pharmacy costs, accommodation costs, action costs, investigation fees, and administrative costs. The cost calculation is one of the strategic steps that must be taken in marketing because it will be used for pricing. Caesarean Section (CS) surgery is one of the largest services and costs a lot in the hospital; careful planning is needed. This study aims to look at the variation in the cost components of CS services in Indonesia based on hospital level, hospital ownership. Methods: This study is a quantitative research Narrative Review by analyzing twenty hospitals in six provinces representing Indonesia from the thesis found in lib.ui database. The analysis in this study is the amount of proportion/variation in the cost components with the type of hospital and hospital ownership. Meanwhile, the criteria for selected hospitals are government-owned and private hospitals with types A, B, C and D. To be able to compare these data and avoid inflation differences, it is necessary to do data collection or valuation presentation (VP). The chosen cases were the usual CS without emergency and complication Results: There was a wide variation in CS service cost components, namely medical services (25% - 90%), accommodation (2% -39%), investigations (1% -36%) and drugs and BHP (2% -50%) both in government and private hospitals. Government-owned type B hospitals and government and private type C costs for medical services are greater than 44%. Conclusion: There are variations in the cost components of CS services at hospital types B and C. There is a need for government efforts to make regulations regarding the magnitude of the ideal cost component as a reference for all hospitals in Indonesia.